Gadjah Mada International Journal Of Business : Factors Affecting Poor Strategy Implementation - Muh. Darmin Ahmad Pella, Ujang Sumarwan, Arief Daryanto, . Kirbrandoko (MM UGM, 2013)
Research on strategy implementation has been developed for three decades, yet only a few studies focus on factors affecting poor strategy implementation. This research evaluates the influence of strategy implementation problems on strategy implementation success and firm performance. This survey was conducted in 60 Indonesian companies and the data were statistically analysed using Structural Equation Modeling Partial Least Square (SEM PLS).